The role of MYEOV gene: a review and future directions - Xi, Yidan; Liu, Xuefei; Ge, Yanan; Jiang, Mingzhe; Zhao, Dong; Zhao, Ershu; Cai, Fei; Wang, Xinlong; Li, Jiatong; Li, Tingting; Zheng, Zhendong (Frontiers in Oncology, 2025)
The overexpressed gene MYEOV in multiple myeloma, as an oncogene, has been widely recognized for its high expression levels in various malignant tumors. MYEOV plays a significant role in multiple malignancies, particularly in diseases such as multiple myeloma, breast cancer, lung cancer, pancreatic cancer, and esophageal cancer. The presence of the open reading frame of MYEOV in humans and other primates suggests its potential protein-coding capacity, although direct evidence of functional MYEOV protein is currently lacking. The role of MYEOV in various tumors is not limited to its direct effects as an oncogene; it also includes its complex role in tumor cell signaling pathways and its ability to participate in miRNA regulatory networks as a competing endogenous RNA (ceRNA). Studies have shown that MYEOV may affect the expression of cancer-related genes through enhancer activity. This article aims to provide a comprehensive review of the role of MYEOV, its involvement in signaling pathways in tumor cells, and the latest advancements in MYEOV-targeted therapies.